Pengaruh Perubahan Organisasi dan Pengembangan Organisasi terhadap Kinerja Karyawan - Evira Yuliana; Ria Marginingsih; Tri Elsa Susilawati (Fakultas Ekonomi Universitas Islam 45, 2020)
The purpose of this study is to study the motivation organizations change and organizations development on the performance of employees of PT Metindo Erasakti, The population in this study is a permanent company, PT Metindo Erasakti, which collected 130 people with a sample of 98 people. For data analysis using statistical tests and calculations using multiple regression with the Product Statistics Service and Solution 23 (SPSS) program. The results of statistical research on the results of research organizations change and organizations development on the performance of employees of PT Metindo Erasakti, this is evidenced by the value of t arithmetic β1 (4,754) with a significance level of 0.000 <α = 0.05 then Ho is rejected and Ha is accepted, and the value of t arithmetic β2 (3,093) with a significant level of 0,001 <α = 0.05 then Ho is rejected and Ha is accepted. The multiple regression equation is obtained with the positive regression coefficients β1 and β2, which means that organizational change and organizational development variable increase the performance results will increase. For the coefficient of determination (KD) = 38,0% means organizational change and organizational development for the performance of employees together with ownership of 38,0% while the remaining 62,0% (100% - 38,0%) is needed by the lying factor. Key word : organization change, organization development, and performance